A Comparison of The Weak-form Efficiency of The Asean Stock Markets Before and During the Covid-19 Pandemic - Kok, Sook Ching; Caroline Geetha (Penerbit UMS, 2023)
This paper aims to examine the weak-form efficient market hypothesis (EMH) for the ASEAN stock markets before and during the outbreak of the COVID-19 pandemic. The pandemic is a tremendous threat to the health condition and mortality of the world population. An important prevention step undertaken was to have social distancing at different levels of strictness. The ongoing pandemic has caused some negative consequences, including businesses enduring a period of hardship and stock market declines. It seems to be expected that a recession is coming ahead and therefore some people are unwilling to invest in the stock market. On the other hand, some people are optimistic about the economy of ASEAN countries and may think that the declines in stock markets are opportunities to invest. They believe in mean reversion that the falls in stock prices are only temporary and the prices will rebound after some time. If this is true, the market is inefficient and stock prices can be predicted. Conversely, if stock price movements are random walks, shocks to prices will be permanent and prices will reach new equilibrium aftershocks. Hence the market is efficient and stock prices are unpredictable. This study analyses the movements of ASEAN stock markets’ composite indices before and during the outbreak of the COVID-19 pandemic to find out whether the markets are efficient and thus cannot be predicted. We found that some ASEAN stock markets were efficient in both periods, while some others were showing decreased or increased efficiency from the period before the pandemic to the period during the pandemic.